1996
DOI: 10.1253/jcj.60.779
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Nitrate Treatment Increases Cardiac Events in Patients With Healed Myocardial Infarction

Abstract: Long-term treatment with nitrates increased cardiac events in patients with healed myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
3
53
0
Order By: Relevance
“…During the 4.3 months of observation in the present study, the incidence of cardiac events in the Continuous group was 3.7%, which was significantly higher than the 0.3% seen in the No-nitrate group. This result is consistent with our earlier randomized prospective study (17) reporting that when 1,002 patients with prior myocardial infarction were observed for 1 8.0 months, the incidence of cardiac events was 6.6% in the group treated with nitrates (mainly continuous ISDNtreatment, 20 mg BID, morning and evening), which was significantly higher than the 3. 1% seen in the untreated group.…”
Section: Effect Of Combining Medicationssupporting
confidence: 92%
“…During the 4.3 months of observation in the present study, the incidence of cardiac events in the Continuous group was 3.7%, which was significantly higher than the 0.3% seen in the No-nitrate group. This result is consistent with our earlier randomized prospective study (17) reporting that when 1,002 patients with prior myocardial infarction were observed for 1 8.0 months, the incidence of cardiac events was 6.6% in the group treated with nitrates (mainly continuous ISDNtreatment, 20 mg BID, morning and evening), which was significantly higher than the 3. 1% seen in the untreated group.…”
Section: Effect Of Combining Medicationssupporting
confidence: 92%
“…Furthermore, a study on 19 healthy volunteers documented that isosorbide mononitrate given over 7 days impaired endothelial function due to formation of free radicals (Thomas et al, 2007). In total, epidemiological evidence indicates that chronic administration of long acting nitrates increase rather than decreases fatal and non-fatal events (Ishikawa et al, 1996;Nakamura et al, 1999). This view is confirmed by experiments on human vascular endothelial cells, which show detNO-induced cell cycle arrest and hypertrophy.…”
Section: Long-term Application Of Detno and Other No Donorsmentioning
confidence: 89%
“…In the Fourth International Study of www.intechopen.com Infarct Survival (ISIS-4), there was no significant reduction in five-week mortality and no survival advantage (ISIS-4 (Fourth International Study of Infarct Survival) Collaborative Group, 1995). Chronic administration of long acting nitrates in patients with healed myocardial infarction resulted in an increased number of patients with cardiac events (Ishikawa et al, 1996) and an increased risk of cardiac deaths occurred in CAD patients with long acting nitrates (Nakamura et al, 1999). Furthermore, a study on 19 healthy volunteers documented that isosorbide mononitrate given over 7 days impaired endothelial function due to formation of free radicals (Thomas et al, 2007).…”
Section: Long-term Application Of Detno and Other No Donorsmentioning
confidence: 99%
“…Nitrate Treatment in VSA AMI. 13, 14 There have been scant studies regarding the relationship between long-term nitrate treatment and cardiac events in VSA patients. Therefore, we performed a prospective cohort study to investigate whether long-term nitrate treatment was beneficial for reducing the incidence of cardiac events in VSA patients.…”
Section: Effect Of Nitrates On Cardiac Events In Patients With Coronamentioning
confidence: 99%